Species distribution and antimicrobial susceptibility of enterococci isolated from broilers infected experimentally with Eimeria spp and feed with diets containing different supplements - Cassenego, Ana Paula Vaz (2011)
Resistant bacteria in animal can be spread to environment and to humans. Poultry feed and infections caused by Eimeria spp. are important factors in determining the intestinal microbial communities. The aim of this study was to verify the prevalence of species and antimicrobial susceptibility of Enterococcus isolated from broilers fed with different supplements and infected experimentally with Eimeria spp. Broilers were divided in eight groups, fed with diets supplemented with a combination of antimicrobial, ionophore-coccidiostatics, probiotic, essential oil. At 14 days old all birds, except the control, received a solution containing oocysts of Eimeria spp. Samples of cloacal swabs from broilers were collected. A total of 240 Enterococcus sp. strains were isolated, confirmed genus by PCR, classified as species, tested for antimicrobial susceptibility and screened by PCR for the presence of tet(L), tet(M) and erm(B) genes. The overall distribution of species isolated from fecal samples was E. faecalis (40%), followed by E. casseliflavus/E. gallinarum (10.8%), E. mundtii (10.8%), E. faecium (10.8%), E. columbae (5.8%) and E. gallinarum (4.2%). Changes in the composition or frequency of Enterococcus species were observed in all dietary supplementation. Antimicrobial susceptibility tests showed resistance phenotypes a range of antibiotics, especially used in humans such as, streptomycin, penicillin, rifampicin and vancomycin. There was no correlation between different supplementation for broilers and antimicrobial resistance and the presence of tet(M), tet(L) and erm(B) genes. Dietary supplementation had effect on the Enterococcus sp. colonization, but did not have significant effect on the phenotype and genotype of antimicrobial resistance in enterococci.